A family of Acrp30/adiponectin structural and functional paralogs - Wong, Guang W. (National Academy of Sciences, 2004)
Biochemical, genetic, and animal studies in recent years have established a critical role for the adipokine Acrp30/adiponectin in controlling whole-body metabolism, particularly by enhancing insulin sensitivity in muscle and liver, and by increasing fatty acid oxidation in muscle. We describe a widely expressed and highly conserved family of adiponectin paralogs designated as C1q/tumor necrosis factor-α-related proteins (CTRPs) 1–7. In the present study, we focus on mCTRP2, the mouse paralog most similar to adiponectin. At nanomolar concentrations, bacterially produced mCTRP2 rapidly induced phosphorylation of AMP-activated protein kinase, acetyl-CoA carboxylase, and mitogen-activated protein kinase in C2C12 myotubes, which resulted in increased glycogen accumulation and fatty acid oxidation. The discovery of a family of adiponectin paralogs has implications for understanding the control of energy homeostasis and could provide new targets for pharmacologic intervention in metabolic diseases such as diabetes and obesity.